Underwater 3D filming - Roberto Rinaldi (SCIRES-IT, 2014)
After an experimental phase of many years, 3D filming is now effective and successful. Improvements are still possible, but the film industry achieved memorable success on 3D movie’s box offices due to the overall quality of its products. Special environments such as space (“Gravity” ) and the underwater realm look perfect to be reproduced in 3D. “Filming in space” was possible in “Gravity” using special effects and computer graphic. The underwater realm is still difficult to be handled. Underwater filming in 3D was not that easy and effective as filming in 2D, since not long ago. After almost 3 years of research, a French, Austrian and Italian team realized a perfect tool to film underwater, in 3D, without any constrains. This allows filmmakers to bring the audience deep inside an environment where they most probably will never have the chance to be.